Comparative Study of Supervised and Semi-Supervised Learning for Enhanced Drug Prediction - Jagadeesan, V; Palanivel, K (International Journal of Computer Sciences and Engineering, 2018)
Several precautions should be taken in using pharmaceutical drugs, for both healthcare professionals, who prescribe and administer drugs, and for drug consumers. Factors such as interactions among the prescribed drugs, interactions with the patient’s current medication, side effects to be avoided, and contraindications, need to be carefully considered. Additionally, the presence of some drug properties, such as side effects and effectiveness, depends on characteristics of patients, such as age, gender, lifestyles, and genetic profiles. The goal is to provide a system to assist medical professionals and drug consumers in choosing and finding drugs that suit their needs. And develop an approach that allows querying for drugs that satisfy a set of conditions. The approach allows users to specify side effects and tailors the answers based on user specification. Finally utilize drug data from multiple data sources. However, drug data are usually noisy and incomplete as they are either manually curated or automatically extracted from text resources such as drug labels. To cope with incomplete and noisy data, data mining techniques were designed and implemented which include clustering and classification algorithms. Then the developed system was used for comparative analysis of supervised and semi-supervised learning using performance metrics. The result shows that Semi-supervised method provided 40% improved response time in comparison with Supervised method in Drug Retrieval System.